Cast iron street furniture: A historical review. Issue 3 (September 2020) - Soffritti, C.; Calzolari, L.; Chicca, M.; Bassi Neri, R.; Neri, A.; Bazzocchi, L.; Garagnani, G.L.
Highlights: Street furniture in cast iron for improving the quality of life in urban settlements. Diffusion of street furniture in relation to the First Industrial Revolution. Artistic, aesthetic and ethical issues, and historical catalogues. Local aspects of street furniture in United Kingdom, France and Italy. Production technique and preservation of street furniture. Abstract: The term "street furniture" indicates objects mostly made of cast iron alloys and aimed to improve the quality of life in urban settlements, such as street lamps, fountains and gazebos. These objects are often ancient and relevant as cultural heritage. Despite the constant presence of street furniture in urban settlements, studies of its evolution along centuries are limited. Since functional aspects have been often considered prevalent against artistic and historical values, many objects have been considered obsolete, thus replaced or re-melted. Street furniture rarely received attention by scholars, and studies on this topic have been often incomplete. This study reviews the history of street furniture made of cast iron (CI street furniture), first examining the reasons behind the choice of this material, closely related to its diffusion during the First Industrial Revolution. The review discusses the relationship between CI street furniture and cultural heritage based on artistic, aesthetic and ethical issues, also examining historical catalogs. The development of CI street furniture in United Kingdom, France and Italy is reported, together with their local aspects. The production technique is discussed and the importance of preservation of CI street furniture is highlighted, emphasizing the need for globally planned interventions in this field.